Translation and validation of the child's challenging behaviour scale version-2 (CCBS-2)/ Mohamad Qayum Mohamad Sabri and Rosilah Wahab - Mohamad Sabri, Mohamad Qayum; Wahab, Rosilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
CCBS-2 was designed to understand the behavioural issues from the mother of children with disabilities' perspective. A behavioural intervention plan was developed through the analysis of available assessment related to behaviour and insight from the mother of the child. Nevertheless, there are limited assessments associated with challenging behaviour that is psychometrically adequate and linguistically appropriate in Malaysia. Thus, there is a need to translate CCBS-2 into the Malay language to be utilised in the clinical practice and providing a better perspective of a child's behaviour. Translation and validation of CCBS-2 were done with a cross-sectional study design. Both forward and backward translation was done by two translators each. Then, preliminary pilot testing was done to identify any issue in the translated instrument. Evaluation of content validity was done using I-CVI, Ave-CVI and modified kappa value. As a result, both phases of translation achieved semantic, linguistic and theoretical equivalence while culturally appropriate for Malay speaker. CCBS-2 Malay also found no major issue during preliminary pilot testing and achieved adequate content validity.